Posterior Reversible Encephalopathy Syndrome (PRES) in the peripartum period - Jayati Nath (Barpeta Obstetrics and Gynaecological Society, 2018)
Posterior Reversible Encephalopathy Syndrome (PRES) is defined as a clinico-pathological disorder characterized by a myriadof symptoms including altered mental status, headaches, blurring of vision and seizure, because of the involvement of the occipital and/or parietal lobes of the brain. Eclampsia is known to be the commonest etiological factors behind PRES. This is a review of literature guided clinic-radiological findings which aid in the early diagnosis and management of PRES and thereby reduce morbidities and complications related to the same.